Investigation on the plasticity accumulation of Ti-6Al-4V fretting wear by decoupling the eﬀects of wear and surface proﬁle in ﬁnite element modelling - Mohd Tobi, A.L.; Sun, W.; Shipway, P.H. (Elsevier Science Ltd, 2017)
A ﬁnite-element-based wear modelling methodology and a computational device for decoupling wear eﬀects is presented in this study. The decoupling of wear eﬀects facilitates the capture of plasticity accumulation on a particular wear-scarring proﬁle after a speciﬁc number of cycles. It was determined that signiﬁcant plasticity accumulation due to plastic shakedown was predicted in a partial-slip case, while a saturation of plastic deformation was predicted in a gross-sliding case. It was also predicted that a signiﬁcant amount of plasticity does not meaningfully contribute to the stress and strain range observed in the contact region. It was assumed that plasticity accumulation contributes towards wear of the material and feeds the stress changes, which indirectly aﬀects fatigue life.